Effectiveness of local sago and moringa leaf based complementary foods and maternal nutrition education in preventing stunting in North Aceh - Dian Vita Sari; Fatmawati Fatmawati; Junaedy Junaedy (AcTion: Aceh Nutrition Journal, 2025)
Malnutrition remains a global challenge with far-reaching health and developmental implications. Indonesia continues to experience a high prevalence of stunting, reaching 31.8%, which highlights the need for effective and sustainable interventions. This study aimed to evaluate the effectiveness of a locally based intervention utilizing Metroxylon sp. (aren sago) and Moringa oleifera (moringa leaves) as complementary food additives combined with maternal nutrition education in reducing stunting. A quasi-experimental study was conducted in North Aceh in July 2025, involving 128 mothers and their stunted children aged 6–24 months old. The intervention consisted of nutrition education on complementary foods made with sago and moringa leaves, delivered through modules and videos, along with a four-week provision of complementary foods. Data were analyzed using the Wilcoxon signed-rank test. The findings demonstrated a significant improvement in the nutritional status of children, with the proportion classified as having a good nutritional status increasing from 43.0% to 84.4%, and no cases of severe malnutrition were identified (p < 0.05). Maternal nutrition knowledge also improved, with 35.2% achieving a “good” score (p < 0.05). In conclusion, locally sourced food-based interventions combined with nutrition education effectively improve children’s nutritional status and strengthen maternal knowledge. This approach is recommended as a contextual and sustainable strategy for stunting prevention